2019
DOI: 10.11648/j.ijnrem.20190405.11
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Nano-formulations of Neem and Peppermint Oils on the Bionomics and Enzymatic Activities of <i>Agrotis ipsilon</i> Larvae (Lepidoptera: Noctuidae)

Abstract: Nanotechnology is considered to be a development way to gain efficient and potential approaches towards pest control. The effect of both neem and peppermint oils as bulk, nano and loaded nano-emulsions have been studied against the different biological aspects of the 2 nd larval instar of Agrotis ipsilon (Hufn.) under laboratory conditions. Their effects on enzymatic activities were investigated for the 2 nd and 4 th larval instars. The effects of adding the different formulations of either neem or peppermint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Digestion is a process of interactions taking place between chemicals (enzymes) produced by the same set of cells of midgut that absorb the nutrients. The activity of selected enzymes including, αamylase, αand β-glycosidase, lipase and general proteases were affected and reduced particularly 72 h post treatment, which supports our previous results that the nutritional reductions follows the lower activity of enzymes (Rharrabe et al, 2008;Khosravi et al, 2010;Hasheminia et al, 2011) and other reports are also indicative in inhibition of important enzymes in their respective studies (Senthil-Nathan, 2013;Amin et al, 2019). George et al (2018) reported the presence of a lectin in Withania leaves which showed insecticidal, growth inhibition and could also damage the secretory cells of midgut.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Digestion is a process of interactions taking place between chemicals (enzymes) produced by the same set of cells of midgut that absorb the nutrients. The activity of selected enzymes including, αamylase, αand β-glycosidase, lipase and general proteases were affected and reduced particularly 72 h post treatment, which supports our previous results that the nutritional reductions follows the lower activity of enzymes (Rharrabe et al, 2008;Khosravi et al, 2010;Hasheminia et al, 2011) and other reports are also indicative in inhibition of important enzymes in their respective studies (Senthil-Nathan, 2013;Amin et al, 2019). George et al (2018) reported the presence of a lectin in Withania leaves which showed insecticidal, growth inhibition and could also damage the secretory cells of midgut.…”
Section: Discussionsupporting
confidence: 85%
“…Detoxification is a phenomenon for reduction of the toxic effects of exogenous compounds that may be received by any organism (Amin et al, 2019). Two important detoxifying compounds are esterases and glutathione-s-transferases.…”
Section: Discussionmentioning
confidence: 99%
“…A. ipsilon is also a major polyphagous pest that damages more than 30 important crops worldwide [ 20 ]. The larvae of A. ipsilon can consume more than 400 cm 2 of foliage during their development [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%